2005
DOI: 10.1016/j.physd.2004.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Joint statistics of amplitudes and phases in wave turbulence

Abstract: Random Phase Approximation (RPA) provides a very convenient tool to study the ensembles of weakly interacting waves, commonly called wave turbulence. In its traditional formulation, RPA assumes that phases of interacting waves are random quantities but it usually ignores randomness of their amplitudes. Recently, RPA was generalised in a way that takes into account the amplitude randomness and it was applied to study of the higher momenta and probability densities of wave amplitudes. However, to have a meaningf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
85
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 22 publications
8
85
0
1
Order By: Relevance
“…Note that the wave turbulence approach permits the description of statistical objects which are more general than the spectra, in particular, the one-mode and multi-mode probability density functions (PDFs) [3,[74][75][76]. The evolution of the one-mode PDF is interesting when the initial statistics has random phases and amplitudes, but is not Gaussian.Also, it predicts solutions with fluxes in the probability space which describe intermittency -an anomalously high probability of strong waves [3,75].…”
Section: Long-time Statistical Evolution Of Weakly Non-linear Wave Symentioning
confidence: 99%
“…Note that the wave turbulence approach permits the description of statistical objects which are more general than the spectra, in particular, the one-mode and multi-mode probability density functions (PDFs) [3,[74][75][76]. The evolution of the one-mode PDF is interesting when the initial statistics has random phases and amplitudes, but is not Gaussian.Also, it predicts solutions with fluxes in the probability space which describe intermittency -an anomalously high probability of strong waves [3,75].…”
Section: Long-time Statistical Evolution Of Weakly Non-linear Wave Symentioning
confidence: 99%
“…More recently, this statistical framework has been nicely revisited using the diagrammatic technique [4] and performing analytical calculations, in the 3-wave case [22][23][24]. Interestingly, many experimental and theoretical results have shown that deviations from wave-turbulence predictions can be found for rare events, e.g.…”
mentioning
confidence: 99%
“…Of course, to have a non-trivial description valid over the nonlinear evolution time, the fields must remain of the RPA type over the nonlinear time in the leading order in ǫ. The proof of this involves considering the full multi-particle PDF and will be published separately because it is rather lengthy and outside of the scope of the present paper [20]. Let us introduce a generating function Z(λ, t) = e λ|a k (t)| 2 , where λ is a real parameter.…”
mentioning
confidence: 99%